Dampak rasa syukur pada keterlibatan kerja sukarelawan: Peran mediasi modal psikologis: Impact of gratitude on volunteer work engagement: Mediating role of psychological capital - Murniasih, Farhanah; Cebba, Abdul Hamid (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2023)
This research is crucial to comprehend and enhance volunteer work engagement in non-profit organizations, emphasizing the mediating role of psychological capital to guide organizations in building and sustaining volunteer contributions by understanding the mechanisms through which gratitude influences work engagement. This study aims to determine the role of psychological capital on gratitude and work engagement in volunteers. The research design used quantitative methods with purposive sampling with 250 respondents, dominated by female respondents with an average age of 18-21 years. Data collection used three questionnaires: 24 items Psychological Capital Questionnaire scale (PCQ), 17 items Utrecht Work Engagement Scale (UWES) and 11 items Gratitude Questionnaire (GQ-6). The validity uses Confirmatory Factor Analysis (CFA) with Lisrel 8.7 and the hypothesis is tested by regression analysis with mediators using PROCESS by Hayes in SPSS Ver. 26. The results showed psychological capital (optimism, hope, self-efficacy, resilience) significantly mediates gratitude and work engagement relationships in volunteers.